Adaptive complex‐EKF‐based DOA estimation for GPS spoofing detection. Issue 2 (1st April 2018) - Kang, Chang Ho; Kim, Sun Young; Park, Chan Gook
Abstract : In this study, a simple but effective spoofing detection method using a global positioning system (GPS) directional antenna is proposed which exploits the difference between the estimated direction‐of‐arrival (DOA) and the measured DOA from a GPS almanac and ephemeris data. The receiving signal's DOA is estimated by using a single antenna power measurement‐based complex extended Kalman filter (EKF) which is a complex valued state space based estimation technique. Furthermore, an adaptive logic is applied to the complex EKF to reduce the effect of the measurement disturbance. To maintain the validity of the proposed algorithm, it is assumed that the spoofer is aware of the target's location, but that its DOA is not perfectly the same as that of the authentic GPS signal. In addition, the orientation of the directional antenna is known by using an attitude and heading reference system that is attached to the antenna, and its antenna radiation pattern is also known. The proposed detection method is evaluated using a theoretical analysis and simulations. It is finally confirmed that the proposed algorithm can detect a spoofing signal according to the different direction angles of the spoofing signal, and especially those with low DOAs.